Frequency of orthostatic hypotension in the Pooled Resource Open-Access ALS Clinical Trials database - C. Quarracino; F. Capani; F. Capani; M. Otero-Losada; G. E. Rodríguez; S. Pérez-Lloret; S. Pérez-Lloret (Frontiers in Neurology)
PurposeTo explore the frequency of orthostatic hypotension (OH) in a large sample of amyotrophic lateral sclerosis patients (ALS).MethodsFrom the PRO-ACT database, data of 1,240 ALS patients were analyzed, focusing on blood pressure and heart rate before and after standing. OH was defined as a drop in systolic/diastolic blood pressure > 20/10 mm Hg within 3 min of standing. Neurogenic OH was diagnosed when the heart rate increase was below 15 bpm in patients not taking medications that could affect this response.ResultsAt baseline, 138 (11.1%) patients showed OH, 76.1% of whom had neurogenic OH. At follow-up, 163 patients (13.1%) had OH, 71.2% with neurogenic OH. Only 22.5% of the patients with OH at baseline had OH at follow-up.ConclusionIn a large sample of ALS patients, OH occurred in 11–13%, pointing to a subgroup that might require special care to avoid related complications.